Implementation of Digital Literature Training on Equality Tutor - Ridwan, Ihwan; Ida, Nur (Journal of Nonformal Education, 2022)
Digital literacy training is a human desire both in the pandemic era and in the new normal era because today's society is faced with a period of industrial revolution, therefore, it is necessary to have innovations carried out by PKBM so that the goals are successful. The goals of this research were to: 1) identify the implementation of digital literacy training at PKBM Sipatuwo Deceng, Parepare City and 2) identify whether the implementation of digital literacy training for equivalence tutors is effective?, the approach and type of research used was a quantitative approach with a statistical evaluation research type, the research location was at the Sipatuwo community learning center in Parepare City, the research period started from September to December 2020, the data analysis used was descriptive statistics and applied the T test with the pired sample T test analysis. The results of the study proved that the application of digital literacy training used 2 methods, namely online and offline. For online learning, the learning module was Google Classroom and for offline, operating Ms. Offices. Digital literacy training run effectively by using the Kirkpatrik evaluation model to see the effectiveness of the digital literacy training program, namely at the reaction level, training participants were satisfied, learning levels, training participants have increased understanding. At the behavior level, training participants had better behavior changes, and made the level of result of the training participants felt the good effects from digital literacy training.